2007
DOI: 10.1038/sj.eye.6702762
|View full text |Cite
|
Sign up to set email alerts
|

Delayed radial keratotomy dehiscence following uneventful phacoemulsification cataract surgery

Abstract: Sir, Delayed radial keratotomy dehiscence following uneventful phacoemulsification cataract surgery A 73-year-old female was referred with cataracts. Bilateral radial keratotomy (RK) had been performed 9 years previously for high myopia; on her left eye this had been supplemented with astigmatic keratotomies. Best-corrected visual acuities were 6/36 right eye and 6/12 left eye. She had bilateral moderate nuclear sclerotic cataracts. Fundoscopy showed healthy discs with a right epiretinal membrane and normal le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Wound dehiscence has been reported during the postoperative course although this is rare. 7 The literature reports increased precision and reproducibility of anterior capsulotomy with laser-assisted cataract surgery over conventional cataract surgery; however, a recent meta-analysis of 3,554 cases found that risks for incomplete capsulotomy, anterior capsulotomy tags, and anterior capsule tears were significantly higher with FLACS in routine cases. [18][19][20][21] The FEMCAT trial (nearly 1500 eyes) found no significant difference in overall clinical outcome between routine phacoemulsification and FSassisted methods, including complication rates in routine eyes, which was further supported by a recent meta-analysis reporting that both methods are safe and effective with no difference in mid-term visual acuity.…”
Section: Discussionmentioning
confidence: 99%
“…Wound dehiscence has been reported during the postoperative course although this is rare. 7 The literature reports increased precision and reproducibility of anterior capsulotomy with laser-assisted cataract surgery over conventional cataract surgery; however, a recent meta-analysis of 3,554 cases found that risks for incomplete capsulotomy, anterior capsulotomy tags, and anterior capsule tears were significantly higher with FLACS in routine cases. [18][19][20][21] The FEMCAT trial (nearly 1500 eyes) found no significant difference in overall clinical outcome between routine phacoemulsification and FSassisted methods, including complication rates in routine eyes, which was further supported by a recent meta-analysis reporting that both methods are safe and effective with no difference in mid-term visual acuity.…”
Section: Discussionmentioning
confidence: 99%
“…14 reported one case with intraoperative RK incision dehiscence during a 3-mm transparent corneal phacoemulsification procedure 30 years after RK. Day and Seward 11 reported a case with no intraoperative dehiscence of the RK incisions during transparent corneal phacoemulsification 9 years after the RK procedure. However, wound leakage was observed in two RK incisions on the first postoperative day.…”
Section: Discussionmentioning
confidence: 99%
“…7 The conventional transparent corneal incision performed for phacoemulsification may lead to dehiscence of the RK incision. [8][9][10][11][12] Once RK incision dehiscence has occurred, phacoemulsification can be continued after suturing the dehiscence. 8,10 It has been suggested that when the spacing between two adjacent RK incisions is large enough to exceed the width of the transparent corneal incision, a transparent corneal incision can be considered for cataract surgery; otherwise, a scleral tunnel incision is recommended to avoid intersecting the RK incisions.…”
Section: Introductionmentioning
confidence: 99%
“…In one case, no dehiscence was noted intraoperatively, but two RK incisions were Seidel positive at post-operative day 1. They were treated with sutures and a bandage contact lens [4]. …”
Section: Discussionmentioning
confidence: 99%
“…Postoperative eye drops or oral medication may be prescribed to reduce intraocular pressure in the immediate post-operative period. Even if the surgery goes well, re-examination is always needed 1 day after the surgery to determine if there is delayed RK incision dehiscence [4]. …”
Section: Discussionmentioning
confidence: 99%